Study of the Association of Some Tumor Markers and Serum Protein Electrophoresis Patterns with Breast Cancer in Iraqi Population - Awachti , Yassin B. Ridha; Sahib, Dina Hamid; Alfaily, Jwan.Y.B.; Mohammed, Zahraa J. (Iraqi Journal of Science, 2025)
Breast cancer is the most commonly diagnosed cancer and a leading cause of cancer mortality among females worldwide. The recruitment of less invasive serum protein electrophoresis and serum breast cancer tumor markers as monitoring factors for patient response to therapy is still controversial. Hence, the present study aimed to designate serum protein electrophoresis pattern of carcinoembryonic antigen (CEA), carcinoma antigens (CA125 and CA 15-3) as novel biomarkers in monitoring breast cancer patients under and post radiotherapy or chemotherapy. Samples included 23 breast cancer women patients after mastectomy and under or post chemotherapy and radiotherapy. Tumor markers CEA, CA 15-3, and CA 125 were measured by using electrochemiluminescence method used in Cobas ®. Total serum protein was performed by using commercially available kits suitable with semiautomated chemistry analyzer. Quantitative estimation of serum proteins was accomplished by agarose serum protein electrophoresis.